Genome-wide meta-analysis identifies novel risk loci for uterine fibroids within and across multiple ancestry groups - Jeewoo Kim; Ariel Williams; Hannah Noh; Elizabeth A. Jasper; Sarah H. Jones; James A. Jaworski; Megan M. Shuey; Edward A. Ruiz-Narváez; Lauren A. Wise; Julie R. Palmer; John Connolly; Jacob M. Keaton; et al. (Nature Communications)
Abstract Uterine leiomyomata or fibroids are highly heritable, common, and benign tumors of the uterus with poorly understood etiology. Previous GWAS have reported 72 associated genes but included limited numbers of non-European individuals. Here, we identify 11 novel genes associated with fibroids across multi-ancestry and ancestry-stratified GWAS analyses. We replicate a known fibroid GWAS gene in African ancestry individuals and estimate the SNP-based heritability of fibroids in African ancestry populations as 15.9%. Using genetically predicted gene expression and colocalization analyses, we identify 46 novel genes associated with fibroids. These genes are significantly enriched in cancer, cell death and survival, reproductive system disease, and cellular growth and proliferation networks. We also find that increased predicted expression of HEATR3 in uterine tissue is associated with fibroids across ancestry strata. Overall, we report genetic variants associated with fibroids coupled with functional and gene pathway enrichment analyses.